Development: experiences, insights and introspection - Sharma, Vipin; Leach, Melissa (fwd.) (Hyderabad Orient Blackswan, 2021)
The book introspects the development process through different lenses historical, social, economic, political, financial and administrative. Dr. Sharma s unique narrative of attempting to find some missing links between development theory and practice stems from his experience as a development administrator and practitioner in the Indian Administrative Service.
Keywords: Public Finance Management; International Finance